Utilização de espuma rígida de tanino na confecção de painéis sanduíche - Corrêa, Ronan (2019)
Rigid polyurethane (PU) foams are the most widespread core materials in the sandwich panel market due to the good structural properties and versatility of applications. However, they are highly flammable materials, release toxic gases and are petroleum derivative. Tannin-based rigid foams (TA) fits as innovative alternative mainly owing great fire resistance, low smoke emission and harmful gases. Therefore, the objective of the study was to evaluate the potential of TA foams for the production of sandwich panels. Thus, for the production of TA foams, tannin extract of Acacia mearnsii De Wild., furfuryl alcohol, distilled water, diethyl ether and 32% sulfuric acid was used. They were homogenized generating a viscous cream which was placed in a mold with MDF faces. For industrial control the material was placed in a hydraulic press at 120°C for 10 min. After, the mold was removed to obtain the MDF sandwich panel. At the comparison level, PU rigid foam sandwich panels were made. The foams and panels made of TA and PU were transformed into specimens and evaluated by means of morphological analysis, physical, mechanical and thermal tests. For morphological characterization of foams, was used pictures scanning electron microscopy (SEM). The evaluated physical properties were moisture content, apparent density, water absorption and swelling in thickness. For evaluation of the mechanical properties were carried out tests of flatwise and edgewise compression and static bending. Thermal properties were also evaluated through thermogravimetric analysis (TGA) and fire resistance. The results shown TA foams have a fragile and brittle cell structure, with a predominance of open cells with a mean diameter of 165.99 μm. Panels with TA foams have high affinity for water and higher bulk density than PU foams. In the mechanical analyzes, the TA panels showed less resistance than the synthetic foam panels. However, the thermal properties of TA foams were higher, presenting good thermal stability and lower mass loss in relation to PU foams, due to the ability of the foams to self-extinguish the flame. In general, TA foams have great potential for use in sandwich panels and replacement of synthetic foams, mainly because of their exceptional fire resistance characteristic and because they are ecologically correct. However, more research needs to be done in order to better the physical and mechanical properties of the material.